Upstairs, downstairs Season 1 [videorecording (DVD)] - Thomas, Heidi, 1967-; Lyn, Euros; Metzstein, Saul, 1970-; Atkins, Eileen, 1934-; Marsh, Jean; Hawes, Keeley, 1976-; Stoppard, Ed (British Broadcasting Corp. : Burbank, CA : Distributed by Warner Home Video Ltd., 2011)
One of the most loved television series of all time is brought back to life with a fresh cast and sumptuous production values. It's 1936, and six years since parlor maid Rose left 165 Eaton Place, when fate brings her back as housekeeper to its new owners: Sir Hallam, his wife Lady Agnes, and Maud, Lady Holland, his mother. Rose soon finds she has her work cut out as she recruits a new 'downstairs' family to help run the elegance and finery of the 'upstairs' world.